The value of oxygen index and base excess in predicting the outcome of neonatal acute respiratory distress syndrome - Hui Wu; Xiaoyang Hong; Yangming Qu; Zhenqiu Liu; Zhe Zhao; Change Liu; Qiong Ji; Jie Wang; Quan Xueli; Sun Jianwei; Dongliang Cheng; Zhi-Chun Feng; et al. (Jornal de Pediatria, 2021)
Objective: This study aimed to identify the predictors and threshold of failure in neonatal acute respiratory distress syndrome. Methods: Newborns with severe acute respiratory distress syndrome aged 0–28 days and gestational age ≥36 weeks were included in the study if their cases were managed with non-extra corporal membrane oxygenation treatments. Patients were divided into two groups according to whether they died before discharge. Predictors of non-extra corporal membrane oxygenation treatment failure were sought, and the threshold of predictors was calculated. Results: A total of 103 patients were included in the study. A total of 77 (74.8%) survived hospitalization and were discharged, whereas 26 (25.2%) died. Receiver operating characteristic analysis of oxygen index, pH, base excess, and combinations of these indicators demonstrated the advantage of the combination of oxygen index and base excess over the others variables regarding their predictive ability. The area under the curve for the combination of oxygen index and base excess was 0.865. When the cut-off values of oxygen index and base excess were 30.0 and −7.4, respectively, the sensitivity and specificity for predicting death were 77.0% and 84.0%, respectively. The model with base excess added a net reclassification improvement of 0.090 to the model without base excess. Conclusion: The combination of oxygen index and base excess can be used as a predictor of outcomes in neonates receiving non-extra corporal membrane oxygenation treatment for acute respiratory distress syndrome. In neonates with acute respiratory distress syndrome, if oxygen index >30 and base excess <−7.4, non-extra corporal membrane oxygenation therapy is likely to lead to death.